2017
DOI: 10.2147/copd.s141852
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of symptoms and comorbidities to the economic impact of COPD: an analysis of the German COSYCONET cohort

Abstract: BackgroundAlthough patients with COPD often have various comorbidities and symptoms, limited data are available on the contribution of these aspects to health care costs. This study analyzes the association of frequent comorbidities and common symptoms with the annual direct and indirect costs of patients with COPD.MethodsSelf-reported information on 33 potential comorbidities and symptoms (dyspnea, cough, and sputum) of 2,139 participants from the baseline examination of the German COPD cohort COSYCONET was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
2
16
0
1
Order By: Relevance
“…A cross-sectional study conducted in the French Initiatives COPD cohort provided evidence that current cough in the previous 7 days was an important determinant of health-related QoL impairment in stable COPD patients 34. Nevertheless, previous studies had not demonstrated association of cough and mucus production with increased direct health care costs in COPD patients 35…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted in the French Initiatives COPD cohort provided evidence that current cough in the previous 7 days was an important determinant of health-related QoL impairment in stable COPD patients 34. Nevertheless, previous studies had not demonstrated association of cough and mucus production with increased direct health care costs in COPD patients 35…”
Section: Discussionmentioning
confidence: 99%
“…These multidimensional factors can strongly contribute to and perpetuate cognitive impairments and psychological symptoms, create barriers to adaptive health behaviours and significantly contribute to the burden of the disease, affecting quality of life often in a downward spiral [11,12]. The net effects are substantial reductions in the quality of life for those with chronic respiratory disease, their families and informal caregivers [12,13], together with high socioeconomic costs [14].…”
Section: The Clinical Relevance Of Psychology and Behaviour Changementioning
confidence: 99%
“…Furthermore, these psychological disorders are often underdiagnosed and undertreated in patients with COPD [8,12,13]. High levels of anxiety and depression are associated with reduced quality of life [14], increased costs to the healthcare system [15,16], and increased mortality [17,18]. Furthermore, anxiety and depression are associated with reduced functional exercise capacity and increased dyspnea [19,20], increased hospitalizations and COPD exacerbations [21,22,23,24], as well as unfavorable health behaviors including reduced self-reported medication adherence [25], and increased levels of smoking and physical inactivity [26].…”
Section: Introductionmentioning
confidence: 99%